Consolidation and high‐temperature strength of monolithic lanthanum hexaboride. Issue 6 (29th January 2022) - Demirskyi, Dmytro; Suzuki, Tohru S.; Yoshimi, Kyosuke; Vasylkiv, Oleg O.
Abstract: In this study we explored the densification, microstructure evolution, and high‐temperature properties of bulk lanthanum hexaboride. LaB6 bulks were consolidated using spark‐plasma sintering only in the temperature range between 1400°C and 1700°C. We adopted flash spark plasma sintering (SPS) of LaB6 using a direct current heating without a graphite die. We observed a peculiar grain‐size gradient when coarse grains exceeding 300 μm were observed on the top side of the specimen, while the bottom side had a grain size of 15–20 μm. Such large grain was not observed using SPS at 2000°C, suggesting that these might originate from a local overheating. Based on the three‐point flexural tests, it was observed that the toughness and strength of the LaB6 were acceptable at room‐temperature (3.1 ± 0.2 MPa m 1/2, 300 ± 20 MPa). However, at 1600°C, these parameters would decrease to 1.3 ± 0.1 MPa m 1/2 and 120 ± 40 MPa, respectively.